High incidence of allograft dysfunction in liver transplanted patients treated with pegylated-interferon alpha-2b and ribavirin for hepatitis C recurrence: possible de novo autoimmune hepatitis?. Issue 2 (23rd June 2006) - Berardi, S; Lodato, F; Gramenzi, A; D'Errico, A; Lenzi, M; Bontadini, A; Morelli, M C; Tamè, M R; Piscaglia, F; Biselli, M; Sama, C; Mazzella, G; et al.
Abstract : Background: Interferon may trigger autoimmune disorders, including autoimmune hepatitis, in immunocompetent patients. To date, no such disorders have been described in liver transplanted patients. Methods: 9 of 44 liver transplanted patients who had been receiving pegylated-interferon alpha-2b and ribavirin for at least 6 months for hepatitis C virus (HCV) recurrence, developed graft dysfunction despite on-treatment HCV-RNA clearance in all but one case. Laboratory, microbiological, imaging and histological evaluations were performed to identify the origin of graft dysfunction. The International Autoimmune Hepatitis scoring system was also applied. Results: In all cases infections, anastomoses complications and rejection were excluded, whereas the autoimmune hepatitis score suggested a "probable autoimmune hepatitis" (score from 10 to 14). Three patients developed other definite autoimmune disorders (overlap anti-mitochondrial antibodies (AMA)-positive cholangitis, autoimmune thyroiditis and systemic lupus erythematosus, respectively). In all cases, pre-existing autoimmune hepatitis was excluded. Anti-lymphocyte antibodies in immunosuppressive induction treatment correlated with the development of the disorder, whereas the use of granulocyte colony-stimulating factor to treat interferon-induced neutropenia showed a protective role. Withdrawal of antiviral treatment and treatment with prednisone resulted in different outcomes (five remissions and four graft failures with two deaths). Conclusions: De novo autoimmune hepatitis should be considered in differential diagnosis along with rejection in liver transplanted patients developing graft dysfunction while on treatment with interferon.